Mapping Indonesian Library and Information Science Research in 2022: A Bibliometric Analysis - Nurhayati, Euis Sri; Mardhotillah, Annisa Ilmi; Rahmi, Rahmi (BACA: Jurnal Dokumentasi dan Informasi, 2025)
This paper scrutinizes the dissemination of research outcomes in the library and information science domain in SINTA-endorsed journals in 2022—the research aimed to unearth novel developments in the field within Indonesia. A quantitative bibliometric approach was employed for this study. The research included 342 papers from 20 journals indexed in SINTA 2-6. Järvelin & Vakkari’s (2022) categorization scheme was used to evaluate the data. The Cohen’s Kappa reliability test resulted in a value of 0.24, reflecting an adequate level of agreement.The study revealed that user education and information literacy instruction were the most frequently discussed topics. Research on interactive (user-centric) Information Retrieval; live or test collection text retrieval methods (inclusive of Cross-Lingual Information Retrieval/CLIR); and retrieval methods for other media types (such as image, video, music, multimedia, and hypermedia) is expected to cease in 2022. The research identified 338 authors contributing to the papers, with Diponegoro University emerging as the most prolific institutional contributor with 45 papers. Qualitative methodology was predominantly used, and keyword analysis results were grouped into 8 clusters. The study concludes that the spread of research themes is uneven, and several unexplored topics warrant attention for future research endeavors.